1997
DOI: 10.1002/(sici)1096-911x(199706)28:6<401::aid-mpo2>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival data and prognostic factors of a complete response to chemotherapy in patients with head and neck cancer treated with platinum-based induction chemotherapy: A hellenic co-operative oncology group study

Abstract: A group of 154 patients with locally advanced head and neck cancer, treated with platinum‐based induction chemotherapy, were followed up for 5 years and several pretreatment characteristics were analyzed for possible correlation to a complete response (CR) to chemotherapy, time to progression (TTP) and overall survival (OS). Clinical stage (p = 0.0125) were selected as important prognostic factors for CR by step‐wise logistic regression. We also identified response to chemotherapy (p = 0.0120), age (p = 0.0066… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…However, scarce evidence is available on whether these risk factors interact with major treatment modalities in HNSCC. Fountzilas et al [ 8 ] reported that absence of smoking history was an important prognostic factor for complete response in 154 patients with locally advanced HNSCC receiving platinum-based induction chemotherapy. Kumar et al [ 10 ] demonstrated that a history of smoking was associated with a poor response to induction chemotherapy and a poor survival rate in patients with oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, scarce evidence is available on whether these risk factors interact with major treatment modalities in HNSCC. Fountzilas et al [ 8 ] reported that absence of smoking history was an important prognostic factor for complete response in 154 patients with locally advanced HNSCC receiving platinum-based induction chemotherapy. Kumar et al [ 10 ] demonstrated that a history of smoking was associated with a poor response to induction chemotherapy and a poor survival rate in patients with oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, tobacco smoking has been recognized as a major risk factor for HNSCC [ 7 ]. Previous studies [ 8 10 ] have reported that smoking was correlated with an inferior survival rate. Moreover, subjects with HNSCC who have a habit of smoking tobacco show a poor response to induction chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco exposure, in addition to being the most significant risk factor for HNSCC overall, is also recognized to negatively impact treatment response and survival [66,67]. It is not unexpected, then, that tobacco use is now emerging as an important independent prognostic factor for HPV-OSCC, predicting cancer progression and risk of death in a dose-dependent fashion [6,68].…”
Section: Survival Modifiersmentioning
confidence: 99%
“…Studies which focus on pre- and post-treatment smoking habit describe an improved course of disease for patients who quit smoking ( 8 , 9 ). In case of treatment with primary or adjuvant radiochemotherapy (RCT), the latter is primarily associated with peritumoral tissue hypoxia-related incomplete response to RT ( 10 ), along with no response to platinum-based induction CT ( 11 ). In case of treatment by surgery only, the positive effect of smoking cessation at the time of diagnosis is attributed to improved wound healing, fewer complications such as pneumonia and a decrease in second primary malignancies ( 12 ).…”
Section: Introductionmentioning
confidence: 99%